2005
DOI: 10.1111/j.1365-2230.2005.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Erosive lichen planus of the vulva: weak circulating basement membrane zone antibodies are present

Abstract: The objective of this study was to investigate whether circulating basement membrane zone (BMZ) antibodies are present in erosive lichen planus (LP) of the vulva. In total, 56 consecutive women with biopsy-confirmed erosive LP of the vulva were recruited from a vulval clinic in a district general hospital and teaching hospital in Oxfordshire. Indirect immunofluorescence (IgG and IgA) was performed on 56 sera, and 15 were tested to IgG subclasses (1-4). Immunoblotting was carried out on salt-split and urea-extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 14 publications
4
41
0
Order By: Relevance
“…A study of 126 women with adult-onset VLP found that autoimmune conditions, mainly thyroid disease, were significantly more frequent in patients with VLP than in examined controls (29% and 11.8% with at least one autoimmune disorder, respectively) [32]. Anti-membrane-zone antibodies chiefly targeting BP180 are present in 61% of erosive LP sera, also suggesting that autoimmune mechanisms may be important in its pathogenesis [32]. The association between LP and hepatitis C has been also studied but the results are contradictory.…”
Section: Aetiologymentioning
confidence: 97%
See 1 more Smart Citation
“…A study of 126 women with adult-onset VLP found that autoimmune conditions, mainly thyroid disease, were significantly more frequent in patients with VLP than in examined controls (29% and 11.8% with at least one autoimmune disorder, respectively) [32]. Anti-membrane-zone antibodies chiefly targeting BP180 are present in 61% of erosive LP sera, also suggesting that autoimmune mechanisms may be important in its pathogenesis [32]. The association between LP and hepatitis C has been also studied but the results are contradictory.…”
Section: Aetiologymentioning
confidence: 97%
“…Like for LS, an autoimmune aetiology of LP is supported by the association with autoimmune disorders, family history of autoimmunity and circulating organ-specific antibodies. A study of 126 women with adult-onset VLP found that autoimmune conditions, mainly thyroid disease, were significantly more frequent in patients with VLP than in examined controls (29% and 11.8% with at least one autoimmune disorder, respectively) [32]. Anti-membrane-zone antibodies chiefly targeting BP180 are present in 61% of erosive LP sera, also suggesting that autoimmune mechanisms may be important in its pathogenesis [32].…”
Section: Aetiologymentioning
confidence: 98%
“…Weak circulating basement membrane zone antibodies have been shown to be present in 61% of patients with erosive lichen planus of the vulva (Cooper et al 2005). Lichen planus-like eruptions can be produced by drugs and are seen in GVHD.…”
Section: Aetiologymentioning
confidence: 99%
“…However, antibasement membrane zone antibodies chiefly targeting BP180 are present in 61% of erosive LP sera, suggesting that autoimmune mechanisms may be important in its pathogenesis. 6 The aim of this study was to investigate the prevalence of autoimmune disease and circulating autoantibodies in adult women with vulval LS and erosive LP of the vulva and to compare these with a control population. …”
mentioning
confidence: 99%